Relationship Between Stance Width Variation During One Repetition Maximum Barbell Hip Thrust Performance and Kicking Speed for Young Elite Silat Athletes - Muhammad Zulqarnain Mohd Nasir; Ali Md Nadzalan; Abdul Muiz Nor Azmi; Mohd Aizzat Adnan (OVS LLC, 2023)
Study purpose. This study aimed to determine the relationship between kicking speed performance and different stance widths during barbell hip thrust (BHT) at one repetition maximum (1RM) scores among young elite Silat athletes. Materials and methods. 15 male and 15 female Silat athletes with at least one year of resistance training experience and a mean age of 21.3 ± 1.2 years participated in this study. The load indicator performance associated with kicking performance was measured using 1RM load during BHT at varying stance widths. The data was analyzed using Pearson correlation tests through the SPSS Version 25 application. Results. A significant correlation was found between stance width, physical characteristics, and performance metrics with a low to moderate relationship. For physical features, weight (r=0.43, p<.05), height (r= 0.64, p<.05), and leg length (r= 0.44, p<.05) show positive relationship. Low to moderate significant relationships were found during WSW-RFK (r=0.39, p<.05) regarding 1RM and kicking performance. No significant correlations were found between NSW or NRW and the observed variables, except for a negative correlation between NRW and strength (r= -0.43, p < .05). There was a significant difference between males vs. females in RFK-NSW, RFK (p=0.006, p< .05), and LFK-NRW (p=0.001, p< .05) in kicking performance. Conclusions. This study revealed that stance width in barbell hip thrusts moderately correlates with physical characteristics and performance in young elite Silat athletes, where wider stances align with physical characteristics and narrower stances align with lower kicking performance. It also highlighted the importance of personalized training due to observed gender differences in kicking speed.